Relation of human cardiac action potential duration to the interval between beats: implications for the validity of rate corrected QT interval (QTc). Issue 1 (January 1987) - Seed, W A; Noble, M I; Oldershaw, P; Wanless, R B; Drake-Holland, A J; Redwood, D; Pugh, S; Mills, C
Abstract : Fourteen patients undergoing routine cardiac catheterisation were paced at a steady frequency; after this test, stimuli were introduced with a variable preceding interval (test pulse interval). The QT interval of the electrocardiogram and the duration of the monophasic action potential of the right ventricle were measured. QT interval is a function of action potential duration; the two variables were very closely correlated in this study. Both these variables increased in duration with increasing test pulse interval. A biphasic response, as previously reported, was not seen. An increase in steady state pacing frequency caused QT interval and action potential duration to decrease for any given R-R interval. When frequency of stimulation was suddenly increased and then maintained, there was an immediate action potential shortening followed by a further more gradual shortening occurring over several minutes. These results imply that a simple correction of QT interval for heart rate (QTc) is inadequate. It is concluded that the relation between action potential duration (or QT interval) and heart rate depends on both the instantaneous interval between beats and the duration of the prevailing heart rate.